ANALISIS RASIO PRFOFITABILTAS DALAM MENILAI KINERJA KEUANGAN PT TRIDJAYA MULIA SUKSES MANADO - Maradesa, Christony; Tuerah, Raykes Hinrich; siging, silvia Hinrich (Journal of Information System, Applied, Management, Accounting and Research; Vol 8 No 4 (2024): JISAMAR (September-November 2024), 2024)
Financial performance is a description of the financial condition of a company. Assessing the financial performance of a company can be done by analyzing financial statements with financial ratio analysis, by analyzing financial statements, it can be seen that the financial performance of PT Tridjaya Mulia Sukses is measured using financial ratios.The research objective, to analyze how the financial performance of PT Tridjaya Mulia Sukses in 2018-2019 and 2022-2024 is measured using financial ratios, namely profitability ratios; Net Profit Margin, Return On Asset, Return On Equity and Gross Profit Margin. This research is qualitative with descriptive methods, research data obtained from the financial statements of PT Tridjaya Mulia Sukses. Based on the results of the analysis, it is concluded that the company's financial performance for 4 years, for Net Profit Margin is not good, for Return On Asset is very good, for Return On Equity is very good and for Gross Profit Margin is not good. In ratios that are not good the company needs to consider making strategic decisions to increase productivity and maximize profits.